Voices from the desks: exploring student experiences in counselor education - Foss-Kelly, Louisa L.; Protivnak, Jake J. (The Journal of Counselor Preparation and Supervision, 2017)
The purpose of the qualitative study was to explore the themes that counselor education master’s students perceived as impacting their experience within a counseling program. Counselor education master’s students provided their perceptions of what they attributed to helping or hindering their progress. Themes identified as impacting their experiences were academic environment, finances, job preparation, self-care, life role balance, support, mentoring and advising, and personal growth. Recommendations are provided for counselor educators to consider when structuring programs and interacting with master’s students.
5 citations (Crossref) [2023-10-31]
Keywords: dept.csp

Counseling strategies for empowering people living in poverty: the I‐CARE model - Foss-Kelly, Louisa L.; Generali, Margaret M.; Kress, Victoria E. (Journal of Multicultural Counseling and Development, 2017)
Poverty has an impact on mental health and the counseling process in profound ways; however, counselors may fail to recognize the importance of poverty in clients' lives. The authors propose a model to help counselors navigate the complexities of counseling clients who are living in poverty. The I-CARE Model may help counselors develop insight about personal biases, acknowledge harsh realities of poverty, remove barriers to growth, and expand on the clients' own strengths.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/133-544-051-528-154 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: I-CARE Model; counseling; counselor; counselors; dept.csp; dura mater; human; human experiment; mental health; model; poverty; socioeconomic status

Making Choices and Reducing Risk (MCARR): School Counseling Primary Prevention of Substance Use - Foss-Kelly, Louisa L.; Generali, Margaret M.; Crowley, Michael J. (Professional Counselor, 2021)
The consequences of adolescent drug and alcohol use may be serious and far-reaching, forecasting problematic use or addictive behaviors into adulthood. School counselors are particularly well suited to understand the needs of the school community and to seamlessly deliver sustainable substance use prevention. This pilot study with 46 ninth-grade students investigates the impact of the Making Choices and Reducing Risk (MCARR) program, a drug and alcohol use prevention program for the school setting. The MCARR curriculum addresses general knowledge of substances and their related risks, methods for evaluating risk, and skills for avoiding or coping with drug and alcohol use. Using a motivational interviewing framework, MCARR empowers students to choose freely how they wish to behave in relation to drugs and alcohol and to contribute to the health of others in the school community. The authors hypothesized that the implementation of the MCARR curriculum would influence student attitudes, knowledge, and use of substances. Results suggest that the MCARR had a beneficial impact on student attitudes and knowledge. Further, no appreciable increases in substance use during the program were observed. Initial results point to the promise of program feasibility and further research with larger samples including assessment of longitudinal impact.
0 citations (Crossref) [2023-10-31] ERIC Number: EJ1312406
Keywords: Adolescents; Counselor Role; Decision Making; Grade 9; Health Behavior; High School Students; Knowledge Level; Prevention; Program Effectiveness; Risk; School Counseling; School Counselors; Student Attitudes; Substance Abuse; Urban Schools; dept.csp; peer-reviewed

Professional involvement - Foss-Kelly, Louisa L.; Moorhead, Holly Hartwig (A Guide to Graduate Programs in Counseling: Second Edition, 2025)
Entering a counselor education program is just the first step in becoming a Professional Counselor, which includes developing a solid Professional Counselor identity and a plan for a fulfilling career. In this chapter, the authors provide a step-by-step plan for understanding key elements of becoming a Professional Counselor, beginning to work as a Professional Counselor, and contributing to the counseling profession. These activities include professional involvement, service, and scholarship as well as other meaningful pursuits for building one's successful career. The authors present a professional involvement pyramid to illustrate how Counselors can engage in professional identity development from graduate school throughout their careers. © Oxford University Press 2025. All rights reserved.
Keywords: Counseling; Counselor education; Professional Counselor; Professional Counselor identity; Professional development; Professional service; dept.csp